The RolB/RolC homolog from sweet potato promotes early flowering and triggers premature leaf senescence in transgenic Arabidopsis thaliana plants - Shkryl, Yury (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.